2017
DOI: 10.15252/embj.201695588
|View full text |Cite
|
Sign up to set email alerts
|

PRDM16 represses the type I interferon response in adipocytes to promote mitochondrial and thermogenic programing

Abstract: Brown adipose has the potential to counteract obesity, and thus, identifying signaling pathways that regulate the activity of this tissue is of great clinical interest. PRDM16 is a transcription factor that activates brown fat-specific genes while repressing white fat and muscle-specific genes in adipocytes. Whether PRDM16 also controls other gene programs to regulate adipocyte function was unclear. Here, we identify a novel role for PRDM16 in suppressing type I interferon (IFN)-stimulated genes (ISGs), includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 74 publications
8
42
0
Order By: Relevance
“…IRF3 represses thermogenic gene expression (22). Interestingly, the thermogenic transcription factor Prdm16 suppresses ISG expression (23). Our data extend these findings by demonstrating that the capacity for thermogenic respiration itself may regulate ISG abundance.…”
Section: Significancesupporting
confidence: 75%
“…IRF3 represses thermogenic gene expression (22). Interestingly, the thermogenic transcription factor Prdm16 suppresses ISG expression (23). Our data extend these findings by demonstrating that the capacity for thermogenic respiration itself may regulate ISG abundance.…”
Section: Significancesupporting
confidence: 75%
“…Studies of several cell types have demonstrated that the type I IFN response is accompanied by an antagonistic suppression of mitochondrially encoded genes (Jovanovic et al, 2015;Kissig et al, 2017). However, those studies relied on data from a single cell type, ignoring the possible generality of the findings.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated substantial suppression of mitochondrial-encoded genes in response to IFN and lipopolysaccharide treatments, which was attributed to either a metabolic shift in oxidative phosphorylation or removal of the entire mitochondrial fraction through mitophagy (Jovanovic et al, 2015;Kissig et al, 2017). However, the generality of these findings in different cell types and their relevance for influenza stimulation remained unknown.…”
Section: Infected Epithelial Cells But Not Other Cell Types Show a mentioning
confidence: 99%
See 1 more Smart Citation
“…PRDM16 is a well-characterized transcriptional co-regulator that plays a pivotal role in both brown and beige adipocyte development and function [50,51]. PRDM16 can repress WAT-specific genes and activate BAT-specific genes [50]. Recent studies have shown that PRDM16 can antagonize IFN signaling in brown adipocytes by binding to the promoters of type I IFN-stimulated genes (ISGs), including STAT1.…”
Section: Browning/beiging Of White Adipose Tissuementioning
confidence: 99%